Do We Need a Change in Road Winter Maintenance to Accommodate for Automated Vehicles? A State-of-the-Art Literature Review Considering Automated Vehicle Technology's Usage of Road Infrastructure During Winter. Issue 10 (October 2021) - Ødegård, Ingvild; Klein-Paste, Alex
For automated vehicles to be allowed to join the modern car fleet, and, in the future, replace human drivers, they must be able to handle adverse weather, including snowy conditions. This literature review focuses on how automated vehicles utilize the road and how this use is suitable for winter maintenance strategies. Where global navigation satellite system (GNSS) service is unavailable, automated vehicles need bare roads to perform relative navigation based on real-time data about lane markings, obstacles, and road infrastructure. Snow-covered tracks hinder vehicle navigation and lane marking detection, which might generate wheel slippage that in turn causes emergency stop and challenging friction estimates. Although the entry of automated vehicles into the car fleet does not demand change in the strategies of winter maintenance, it does demand higher level of service than today. Maintaining an entire road network on which autonomous vehicles always can operate is tremendously expensive and likely not feasible. One solution could be to add another maintenance class in a bare road strategy, that is, an automated vehicle maintenance class with a high level of service and a set of operational criteria allowing automated vehicles to operate. The maintenance class should be used for certain main routes where there is a high frequency of automated vehicles. A model that recommends preferable routes to the destination based on current road conditions within the operational envelope should be provided to the automated vehicle system.